Imidazopyridine, a promising scaffold with potential medicinal applications and structural activity relationship (SAR): recent advances. Issue 24 (26th December 2022) - Khatun, Samima; Singh, Abhinav; Bader, Ghulam N.; Sofi, Firdoos Ahmad
Abstract: Imidazopyridine scaffold has gained tremendous importance over the past few decades. Imidazopyridines have been expeditiously used for the rationale design and development of novel synthetic analogs for various therapeutic disorders. A wide variety of imidazopyridine derivatives have been developed as potential anti-cancer, anti-diabetic, anti-tubercular, anti-microbial, anti-viral, anti-inflammatory, central nervous system (CNS) agents besides other chemotherapeutic agents. Imidazopyridine heterocyclic system acts as a key pharmacophore motif for the identification and optimization of lead structures to increase medicinal chemistry toolbox. The present review highlights the medicinal significances of imidazopyridines for their rationale development as lead molecules with improved therapeutic efficacies. This review further emphasis on the structure–activity relationships (SARs) of the various designed imidazopyridines to establish a relationship between the key structural features versus the biological activities. Communicated by Ramaswamy H. Sarma